EULER CHARACTERISTIC OF TANGO BUNDLES - Nguyen, Hong Cong (Trường Đại học Đà Lạt, 2023)
We are interested in a vector bundle constructed by Tango (1976). The Tango bundle is an indecomposable vector bundle of rank n-1 on the complex projective space P^n. In particular, we show that the Euler characteristic of the Tango bundle on P^n is equal to 2n-1.